Avaliação da dolomita funcionalizada para remoção de H2S em gás natural - Oliveira, Rosane Maria Pessoa Betânio (2008)
The natural gas is an alternative source of energy which is found underground in porous and permeable rocks and being associated or not to the oil. Its basic composition includes methane, other hydrocarbon and compounds such as carbon dioxide, nitrogen, sulphidric gas, mercaptans, water and solid particles. In this work, the dolomite mineral, a double carbonate of calcium and magnesium whose the chemical formula is CaMg(CO3)2, was evaluated as adsorbent material. The material was characterized by granulometric analysis, X-ray fluorescence, X-ray diffraction, thermogravimetric analysis, differential thermal analysis, specific surface area, porosity, scanning electronic microscopy and infrared spectroscopy. Then the material was functionalized with diethanolamine (dolomite+diethanolamine) and diisopropylamine (dolomite+diisopropylamine). The results indicated that the adsorbents presented appropriate physiochemical characteristics for H2S adsorption. The adsorption tests were accomplished in a system coupled to a gas chromatograph and the H2S monitoring in the output of the system was accomplished by a pulsed flame photometric detector (PFPD). The adsorbents presented a significant adsorption capacity. Among the analyzed adsorbents, the dolomite+diethanolamine presented the best capacity of adsorption. The breakthrough curves obtained proved the efficiency of this process